Implementasi Akad Mudharabah dalam Perbankan Syariah - Rizal Ancu; Asriani Asriani; Lince Bulutoding (Pusat Riset dan Inovasi Nasional, 2025)
Mudharabah contract is a key instrument in Islamic banking based on profit-sharing principles and free from interest (riba). This study analyzes the implementation of mudharabah, its supporting and inhibiting factors, and its impact on the development of Islamic banking. The findings reveal challenges such as limited human resources and low financial literacy in Islamic finance, yet mudharabah promotes financial inclusion, product diversification, as well as improvement of competence and customer trust. Enhancing education and human resource development is essential for the successful application of mudharabah to strengthen the Islamic economy.